Effect of “Time To Surgery” on the Endometrial Cancer Prognosis - Celik, Engin; Yumru Celiksoy, Harika; Sozen, Hamdullah; Goksever Celik, Hale; Onder, Semen; Salihoglu, Mehmet Yavuz; Topuz, Samet (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: Endometrial cancer is the most common gynecological cancer in developed countries. Our study aims to determine the effect of the time between diagnosis and surgery of endometrial cancer on the prognosis of the disease. STUDY DESIGN: Patients who were diagnosed with epithelial type endometrial cancer and did not receive preoperative chemotherapy, radiotherapy, or hormonal therapy were included in the study. RESULTS: Two hundred eighty-five patients were included in the study. We divided the patients into two groups regarding before and after 8 weeks from diagnosis to surgery. Clinical characteristics of the patients were comparable between the groups, except for comorbid conditions and body mass index. Using cox-regression analysis, time to operation did not have a significant effect on both recurrence and cancer-associated death risk. The log-rank test analysis also showed that there was no significant difference in progression-free survival and disease-specific survival between the patients. There was no significant difference between the groups in terms of progression-free survival and disease-specific survival for cases with endometrioid type grade 1-2 tumors. There was also no significant difference between the groups regarding progression-free survival and disease-specific survival in the patients with tumors of endometrioid type grade 3 and non-endometrioid histology. CONCLUSION: Time delay between diagnosis to surgery of the patients with endometrial cancer has no prognostic importance for recurrence and survival outcomes.